Dying to Go Green: The Introduction of Resomation in the United Kingdom - Georgina M. Robinson (Religions, 2021)
In an age where concern for the environment is paramount, individuals are continuously looking for ways to reduce their carbon footprint—does this now extend to in one’s own death? How can one reduce the environmental impact of their own death? This paper considers various methods of disposing the human body after death, with a particular focus on the environmental impact that the different disposal techniques have. The practices of ‘traditional’ burial, cremation, ‘natural’ burial, and ‘resomation’ will be discussed, with focus on the prospective introduction of the funerary innovation of the alkaline hydrolysis of human corpses, trademarked as ‘Resomation’, in the United Kingdom. The paper situates this process within the history of innovative corpse disposal in the UK in order to consider how this innovation may function within the UK funeral industry in the future, with reference made to possible religious perspectives on the process.